Inequalities in Access to Employment and the Impact on Wellbeing: A Criterion for Spatial Planning? - Liv Osland; Kenneth Gibb; Gwilym Pryce (European Regional Science Association (ERSA), 2010)
This paper attempts to address three questions: (1) How unequal is access to employment and the wellbeing associated with it? (2) What is the money value consumers place on access to employment? and (3) How does the inequality of access to employment correspond to the geographical pattern of variation in social deprivation? On the basis that house prices, once adjusted for property type and size, reflect variation quality of life across space, econometric estimates of the impact of employment access on house prices can be used to simulate the impact on inequality of wellbeing. With this rationale in mind, we use the Osland and Pryce (2009) house price model to derive an appropriate measure of Access Welfare - the wellbeing associated with locating at a given distance to employment - and to put a money value on that welfare. The model also allows us to incorporate the negative externalities associated with living in close proximity to centres of employment, and the complexities that arise from the existence of multiple employment centres of varying size. We use Gini and Atkinson coefficients and kernel density estimation to analyse the inequalities observed.
Keywords: 330